Answer:
A. is the correct answer
Step-by-step explanation:
a=b(1/c-1/d)
Answer: c = b/(a + 1).
Step-by-step explanation:
a = b(1/c - 1/d)
Expand RHS by first finding LCM
a = b((d — c)/cd)
a = (bd — bc)/cd
Then cross multiply
acd = bd — cd
Collect the terms having c to the LHS
acd + cd = bd
Factorise cd out of LHS
( a+ 1)dc = bd
c = bd/(a + 1)d
c = b/(a + 1).
Answer:
36 in.
Step-by-step explanation:
Step 1:
Area = Length × Width Equation
Step 2:
6 × 6 Multiply
Answer:
36 inches
Hope This Helps :)
Answer:
1
Step-by-step explanation:
Anything raised to 0 is 1
Answer:
23rd term of the arithmetic sequence is 118.
Step-by-step explanation:
In this question we have been given first term a1 = 8 and 9th term a9 = 48
we have to find the 23rd term of this arithmetic sequence.
Since in an arithmetic sequence
here a = first term
n = number of term
d = common difference
since 9th term a9 = 48
48 = 8 + (9-1)d
8d = 48 - 8 = 40
d = 40/8 = 5
Now
= 8 + (23 -1)5 = 8 + 22×5 = 8 + 110 = 118
Therefore 23rd term of the sequence is 118.
Answer:
2.45
Step-by-step explanation:
3.50
3-1= 2
50-15= 45
3.50 -1.15= 2.45